The ICT use in the implementation of Directive 2011/24/EU - Borges, A.P. (2013)
This article has as main objective to evaluate the role of information and communication technologies (ICTs), in particular the eHealth (electronic health), in the implementation of the directive 2011/24/EU, of the European Parliament and of the Council of March 9th, on the exercise of patients' rights in cross-border healthcare within Member States of European Union. Being currently underway the deadline for transposition of the Directive, it is important to analyze the probable results for national health systems. Innovatively, the Directive specifically proposes the implementation of a European network of eHealth in the provision of cross-border healthcare. Within ICT, we focus on telemedicine as a key tool for the implementation, on a context of public budgets constrains. In this context, it is assumed that the EU will support and promote cooperation and the exchange of scientific information between member states within the framework of a voluntary network composed by the national authorities responsible for health (or eHealth). We apply the S.W.O.T. (strengths and weaknesses, opportunities and threats) analysis to forecast the main points that should be focused on deeper research. We discuss the technological, economic and social aspects of the use of ICT on the implementation of the directive. It is thus important to evaluate the context of ICT by S.W.O.T. tool to define strategies to sensitize policy-makers, health managers, and citizens, in order to be able to turn threats into opportunities and mitigating the weaknesses in the implementation of the Directive and to promote a better healthcare access for citizens, ensuring safe, effective healthcare and with different quality.